A heat transfer tube wear reliability analysis method based on first-order reliability method. Issue 6 (6th August 2020) - Chen, Xiao; He, Xing; Tang, Lichen; Li, Yuebing; Zhou, Mingjue; Jin, Weiya; Gao, Zengliang
Abstract: The heat transfer tube is one of the most essential components of the nuclear power plant as the boundary between the first and second circuit pressures. The wear between the heat transfer tube and the support plate or the anti-vibration strip is one of the essential reasons for its failure. Based on a heat transfer tube wear analysis method, combined with the reliability analysis theory, the calculation scheme of tube wear failure probability is proposed in this paper. In the analysis and calculation process, the key factors affecting the reliability are determined, including the baffle thickness B and the aperture difference Ce . In the manufacturing process, these key factors can be controlled, which is instructive for engineering practice. Graphical Abstract: